2018
DOI: 10.2174/0929867324666170404145656
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Approaches for Production of Anti-Cancerous Compounds Resveratrol, Podophyllotoxin and Zerumbone

Abstract: Secondary metabolites from numerous plant sources have been developed as anti-cancer reagents and compounds such as resveratrol, podophyllotoxin and zerumbone are of particular importance in this regard. Since their de novo chemical synthesis is both arduous and commercially expensive, there has been an impetus to develop viable, biotechnological methods of production. Accordingly, this review focuses on recent developments in the field, highlighting the use of micropropagation, cell suspension cultures, callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Data showed that Res could relieve the gossypol-induced apoptosis of spermatogenic cells in a low concentration such as 10 μM, which has potential applications in the mitigation of feed toxicity and chemotherapy side-effect. With the development of biotechnological approaches for Res production [ 40 ], compared with the traditional methods to remove the gossypol from cottonseed, it is economic and good effect for large-scale application in Res added directly.…”
Section: Discussionmentioning
confidence: 99%
“…Data showed that Res could relieve the gossypol-induced apoptosis of spermatogenic cells in a low concentration such as 10 μM, which has potential applications in the mitigation of feed toxicity and chemotherapy side-effect. With the development of biotechnological approaches for Res production [ 40 ], compared with the traditional methods to remove the gossypol from cottonseed, it is economic and good effect for large-scale application in Res added directly.…”
Section: Discussionmentioning
confidence: 99%
“…The roots were incubated in flasks containing 25-ml MS media in a rotary shaker running at 100 rpm in the dark. [35]. L. flavum hairy roots were cocultured with P. hexandrum cell suspension cultures in a dual 500-ml shaker flask with the bottom side openings linked by a 4-5 cm length of 3 mm silicone tubing.…”
Section: Precursor Feedingmentioning
confidence: 99%
“…Biotransformation approach of podophyllotoxin production has helped to develop the derivatives of this resin, which have enhanced the anticancer properties coupled with the antimitotic activity of podophyllotoxin. So, Rajesh et al initiated the Agrobacterium-mediated biotransformation of P. hexandrum for increased production of podophyllotoxin [35]. Mature seeds of the plant were collected from its natural habitat, washed with running tap water, and then rinsed with 0.1% (v/v) Teepol solution.…”
Section: Biotransformationmentioning
confidence: 99%
“…Currently, cell culture brought to industrial scale is one of the major commercial sources of taxol. Resveratrol is a naturally occurring polyhydroxystilbene with several important biological and pharmacological properties generally produced in low amounts in a few plant species such as Vitis vinifera, Arachis hypogaea, and mulberries through phenylpropanoid pathway [125]. Resveratrol extracted from conventional cell suspension cultures and callus cultures of A. hypogaea or V. vinifera are in relatively low amounts [26,125].…”
Section: Sm Production In Unorganized Undifferentiated Callus and Celmentioning
confidence: 99%
“…Resveratrol is a naturally occurring polyhydroxystilbene with several important biological and pharmacological properties generally produced in low amounts in a few plant species such as Vitis vinifera, Arachis hypogaea, and mulberries through phenylpropanoid pathway [125]. Resveratrol extracted from conventional cell suspension cultures and callus cultures of A. hypogaea or V. vinifera are in relatively low amounts [26,125]. Several novel biotechnological approaches such as optimization of culture medium and conditions, utilization of different elicitor molecules, establishment of HRC, and genetic manipulation of the resveratrol biosynthesis pathway have been developed to optimize resveratrol production [26,[123][124][125][256][257][258].…”
Section: Sm Production In Unorganized Undifferentiated Callus and Celmentioning
confidence: 99%